Paliperidone is associated with reduced risk of severe hepatic outcome in patients with schizophrenia and viral hepatitis: A nationwide population-based cohort study. (November 2019) - Chang, Chun-Hung; Lane, Hsien-Yuan; Liu, Chieh-Yu; Chen, Shaw-Ji; Lin, Chieh-Hsin
Highlights: To our knowledge, this is the first study to analyze subsequent risk of severe hepatic outcome and paliperidone exposure in schizophrenic patients with viral hepatitis. The results of this nationwide, population-based cohort study showed that (1) receiving paliperidone treatment was associated with reduced risk of SHO in schizophrenic patients with viral hepatitis (aHR 0.155, 95% confidence interval, 0.032–0.737; p  = 0.019); (2) early use of paliperidone was associated with lower risk because of none of paliperidone cohort developed SHO if they received paliperidone treatment within 180 days following schizophrenia diagnosed; (3) more than 90% of SHO developed within five years following schizophrenia diagnosed. Abstract: Objective: Paliperidone, a second-generation antipsychotic, has been found to have minimal hepatotoxicity in patients with schizophrenia. However, long-term hepatic outcome in patients with schizophrenia and viral hepatitis remains unclear. Methods: Data obtained from the Taiwan National Health Insurance Research Database was used to enroll newly diagnosed schizophrenic patients between January 2007 and December 2013. Patients with schizophrenia and viral hepatitis who were receiving paliperidone were allocated to the paliperidone group while those who were not receiving paliperidone were allocated to the control group. Using a 1:2 ratio, we matched the age, sex, and index year to select the control participants. Patients with severe hepatic outcomes (SHOs) before enrollment were excluded. The two groups were studied until December 31, 2013. The primary endpoint was the occurrence of SHOs including liver failure, liver decompensation, liver transplantation, or liver cancer. Results: We identified 134 patients with schizophrenia and viral hepatitis who received paliperidone and 268 matched patients who did not receive paliperidone. Of the 402 patients, 22 (5.47%) developed SHOs during a mean follow-up period of 3.57 ± 1.62 years, including 2 (1.49%) from the paliperidone cohort and 20 (7.46%) from the control group. Furthermore, the Cox multivariate proportional hazards analysis revealed that the risk decreased with paliperidone use (adjusted hazard ratio [HR]: 0.155, 95% confidence interval [CI]: 0.032–0.737, p  = 0.019) after adjusted for confounding factors. Conclusion: Paliperidone treatment was associated with a reduced risk of SHOs in patients with schizophrenia and viral hepatitis.